(untitled) (Quinto Sol, 2022)
In this article, we reconstruct land, water, and planning policies, which are emblematic of the formation of statehood by provincial governments under the first two presidencies of Juan Domingo Perón (1946-1955), in Salta, Argentina. These policies allow us to think about and tackle the process of formation of the provincial State, as well as to investigate the restructuring of power relations, and the disputes and tensions regarding the ways of doing politics in Salta. We reflect on the creation of problems and objects of government intervention, the concentration of land and water, the lack of "technical-administrative" organization of the state apparatus and provincial finances, and the way in which public resources had been managed until then. We focus on the policies and measures of the provincial State, unprecedented in Salta, which sought to address and modify such "problems". These include the creation and reorganization of specific state dependencies, the conducting of economic and social surveys in the provincial territory, the creation and implementation of tax reforms, the measurement and organization of land and agricultural exploitation, and the regulation of water use.